1973
DOI: 10.1111/j.1467-8306.1973.tb00918.x
|View full text |Cite
|
Sign up to set email alerts
|

Solar Radiation and Urban Heat Islands

Abstract: A model which attempts to simulate urban absorption of solar radiation is concerned with direct solar radiation, diffuse sky radiation, diffuse radiation reflected by buildings and streets, and the shortwave energy absorbed by typical urban structures. The ratio between solar radiation absorbed by three-dimensional building-street systems and two-dimensional horizontal surfaces under cloudless conditions indicates that cities undergo great variations with latitude and season. High structure systems absorb more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1
1

Year Published

1980
1980
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(26 citation statements)
references
References 1 publication
0
24
1
1
Order By: Relevance
“…However, evidence indicating the importance of urban geometry to the creation and the magnitude of the UHI phenomenon began to accumulate in the 1970s. Terjung & Louie (1973) were among the first to suggest that the urban-rural daytime temperature anomaly is largely attributable to the aspect of vertical surfaces to the sun.…”
Section: Urban Morphology and Climatementioning
confidence: 99%
“…However, evidence indicating the importance of urban geometry to the creation and the magnitude of the UHI phenomenon began to accumulate in the 1970s. Terjung & Louie (1973) were among the first to suggest that the urban-rural daytime temperature anomaly is largely attributable to the aspect of vertical surfaces to the sun.…”
Section: Urban Morphology and Climatementioning
confidence: 99%
“…The latter strongly correlates spatially with absorbed solar radiation. Such a 'doughnut effect' has previously been reported by Ludwig (1970) and Terjung and Louie (1973). This does not predict a complete maximum heating ring, but distinctive areas of strong convection occur along most margins of downtown.…”
Section: Of the City's Energy Budgetmentioning
confidence: 66%
“…It has been shown that the ratio between solar radiation absorbed by threedimensional building systems and two-dimensional horizontal surfaces under cloudless conditions varies considerably with latitude and season [ 17]. Fig.…”
Section: Concrete Plain Versus Canopy Plainmentioning
confidence: 99%